Study of ten cases of epidemic encephalitis lethargica - Grossman, Morris (1921)
The appearance in epidemic form of a rare disease that profoundly affects the central nervous system has raised during the past three years, much interest in the scientific world. This disease has been studied more earnestly in Austria and Australia, where it appeared in 1917 and in England, France and the United States, where he appeared later.